Mathematics Reform and Teacher Quality in Elementary Grades: Assessments, Teacher Licensure, and Certification - Georges, Annie; Borman, Kathryn M.; Lee, Reginald S. (Education Policy Analysis Archives, 2010)
We analyzed the gap in mathematics standards, assessments and accountability, and teacher licensure and certification requirements in mathematics for elementary grades. We found states delineated mathematics academic standards in specific content areas. Licensure and certification requirements were weak indicators since they lacked the specificity of conceptual and procedural knowledge that could strengthen mathematics content knowledge and inform instructional practices. The most recent changes in licensure and certification requirements intended to affect teacher quality are not reaching a large proportion of elementary teachers; thus, their overall impact on teacher quality is likely to be limited. We discuss policy strategies for licensure and certification requirements likely to have a broader reach in addressing teacher quality at the elementary grades.